The combination of experimental periodontitis and oral microbiota from periodontitis patients aggravates liver fibrosis in mice - Bai, Lan; Wang, Yong‐Li; Chen, Yan‐Lin; Li, Hu‐Xiao; Zhu, Shi‐Wei; Liu, Yan; Song, Zhong‐Chen; Duan, Sheng‐Zhong (Journal of clinical periodontology, 2022)
Aim Periodontitis (PD) is the sixth most prevalent disease around the world and is involved in the development and progression of multiple systemic diseases. Previous studies have reported that PD may aggravate liver injuries. The objective of this study was to investigate whether and how PD affects liver fibrosis. Materials and Methods Ligature‐induced PD (LIP) was induced in male C57/B6J mice, and sub‐gingival plaques (PL) from patients with PD were applied to mouse teeth. Liver fibrosis was induced by carbon tetrachloride (CCl4) injection. The mice were randomly divided into six groups: Oil, Oil+LIP, Oil+LIP+PL, CCl4, CCl4+LIP, and CCl4+LIP+PL. Alveolar bone resorption was evaluated by methylene blue staining. Hepatic function was analysed by serum alanine aminotransferase and hepatic hydroxyproline. Picrosirius red and α‐smooth muscle actin (SMA) staining were used to evaluate the fibrotic area. RNA sequencing and quantitative RT‐PCR were used to measure gene expression. Western blotting was used to measure protein levels. Flow cytometry was used to analyse the accumulation of immune cells. Mouse microbiota were analysed using 16S rRNA gene sequencing. Results Mice in the CCl4+LIP+PL group displayed higher serum alanine aminotransferase and hepatic hydroxyproline as well as more Picrosirius red‐positive and α‐SMA‐positive areas in liver samples than those of the CCl4 group, suggesting that PD (LIP+PL) aggravated CCl4‐induced hepatic dysfunction and liver fibrosis. Consistently, the expression of fibro‐genic genes and the protein levels of transforming growth factor β were much higher in the CCl4+LIP+PL group than in the CCl4 group. Flow cytometry revealed that PD increased the accumulation of immune cells, including Kupffer cells, B cells, and Th17 cells, in the liver of mice with CCl4 treatment. PD also increased the expression of inflammatory genes and activated pro‐inflammatory nuclear factor‐kappa B pathway in the livers of CCl4‐injected mice. Moreover, PD altered both oral and liver microbiota in CCl4‐injected mice. Conclusions PD aggravates CCl4‐induced hepatic dysfunction and fibrosis in mice, likely through the increase of inflammation and alteration of microbiota in the liver.